2004
DOI: 10.1016/j.cub.2004.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Reprogramming of Human Somatic Cells by Xenopus Egg Extract Requires BRG1

Abstract: Animal cloning by nuclear transplantation in amphibia was demonstrated almost half a century ago and raised the question of the mechanisms and genes involved in nuclear reprogramming. Here, we demonstrate nuclear reprogramming of permeabilized human cells using extracts from Xenopus laevis eggs and early embryos. We show upregulation of pluripotency markers Oct-4 and germ cell alkaline phosphatase (GCAP) in 293T cells and human primary leukocytes. Reprogrammed leukocytes had a limited life span and did not exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(139 citation statements)
references
References 34 publications
4
130
1
4
Order By: Relevance
“…Transcriptional activation of Oct4 in mouse fibroblasts treated with ES cell extract requires ATP hydrolysis, most likely for nuclear import of transcription factors Landsverk et al, 2002) and for the activity of chromatin remodeling complexes (Kingston and Narlikar, 1999;Aalfs et al, 2001). Oct4 activation by ES cell extract or Xenopus egg extract also requires the Brg1 subunit of the SWI/SNF complex (Hansis et al, 2004;Taranger et al, 2005). Promoter-specific targeting of SWI/SNF may involve H3K4 (hyper)methylation on OCT4 and NANOG and prime the loci for further transcription-permissive remodeling (H3K4 methylation per se is not sufficient to allow transcription as H3K4 is methylated on both OCT4 and NANOG in 293T cells).…”
Section: Molecular Biology Of the Cell 1550mentioning
confidence: 99%
“…Transcriptional activation of Oct4 in mouse fibroblasts treated with ES cell extract requires ATP hydrolysis, most likely for nuclear import of transcription factors Landsverk et al, 2002) and for the activity of chromatin remodeling complexes (Kingston and Narlikar, 1999;Aalfs et al, 2001). Oct4 activation by ES cell extract or Xenopus egg extract also requires the Brg1 subunit of the SWI/SNF complex (Hansis et al, 2004;Taranger et al, 2005). Promoter-specific targeting of SWI/SNF may involve H3K4 (hyper)methylation on OCT4 and NANOG and prime the loci for further transcription-permissive remodeling (H3K4 methylation per se is not sufficient to allow transcription as H3K4 is methylated on both OCT4 and NANOG in 293T cells).…”
Section: Molecular Biology Of the Cell 1550mentioning
confidence: 99%
“…Hakelien et al (2002) reported the reprogramming of 293T fibroblasts in vitro by extract of Jurkat cells into cells that partially resembled T-lymphocytes and to cells with some characteristics of neurons using a neuronal cell precursor extract. Hansis et al (2004) exposed human 293T kidney cells and primary leukocytes to Xenopus oocyte extract and detected up-regulation of the pluripotency markers alkaline phosphatase and Oct4. Two candidate reprogramming molecules in Xenopus oocyte extract have been identified, the chromatin remodeling ATPase, BRG1 (Hansis et al, 2004), and a tumor-associated protein, Tpt1 (Koziol et al, 2007).…”
Section: Further Research On Ips Cellsmentioning
confidence: 99%
“…Hansis et al (2004) exposed human 293T kidney cells and primary leukocytes to Xenopus oocyte extract and detected up-regulation of the pluripotency markers alkaline phosphatase and Oct4. Two candidate reprogramming molecules in Xenopus oocyte extract have been identified, the chromatin remodeling ATPase, BRG1 (Hansis et al, 2004), and a tumor-associated protein, Tpt1 (Koziol et al, 2007). Antibody depletion of BRG1 from the extract abolished its reprogramming activity.…”
Section: Further Research On Ips Cellsmentioning
confidence: 99%
“…As mentioned before, one other advantage of the Xenopus system is the large amount of material available, opening the way for biochemical analysis of oocyte/egg components. By combining oocyte extract analysis and nuclear transfer, it was shown that Oct4 reactivation required the activity of several components of the oocyte such as the chromatin remodelling factor Brg1 (Hansis et al, 2004) and the transcription factor Tpt1 (Koziol et al, 2007).…”
Section: Nuclear Transfer Strategies Using Xenopus Eggs and Oocytesmentioning
confidence: 99%